The clinic importance of bilirubin parameters in ankylosing spondylitis: Case control study - Koca, Tuba Tülay; Çetin, Gözde Yıldırım; Göğebakan, Hasan; Nacitarhan, Vedat (Journal of Surgery and Medicine, 2018)
Aim: Ankylosing spondylitis (AS) is a chronic disease featuring axial changes, peripheral arthritis and systemic involvement. AS is not only characterized by the strongest genetic contribution for any complex rheumatological disease but is also influenced by environmental and immunological factors. Various proinflammatory cytokines such as tumor necrosis factor (TNF), interleukin- (IL-) 1, IL-6, IL17/28 are probably involved in AS pathogenesis. Recent years IL -23 / IL-17 pathway in the disease pathogenesis has been shown. Bilirubin (Bb) was known to be the end product of hem catabolic pathway, but it was the subject of various studies with antioxidant, anti-inflammatory and immunomodulatory properties in the last decade. Here, the clinic importance of serum Bb parameters in AS patients has been analyzed. Methods: The study designed as case-control. One hundred (N=100) patients with axial AS diagnosed by 2010 Assesment in Ankylosing Spondylitis International Society (ASAS) Classification Criteria were included to the study. Control group was consisted of 75 patients of similar age, gender and BMI. Participants’ age, gender, body mass index (BMI), disease acitivity scores and laboratory data were recorded from the hospital data. Disease activity evaluated by Bath Ankylosing spondylitis disease activity index (BASDAI), Bath Ankylosing spondylitis functional index (BASFI) and Ankylosing spondylitis disease activity score-C-reactive protein (ASDAS_CRP). For these three scores, automatic calculation formulas were used on Internet. ASDAS_CRP>3.5 were accepted as cut-off value for high disease activity. Serum direct Bb, indirect Bb, total Bb, aspartat aminotransferase (AST), alanin aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), gamma glutamyl transferase (GGT), amylase, lipase, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values were recorded from the hospital records. Results: The study included 100 AS patients at mean age of 37.9 ± 12 years, 75 controls at mean age of 39.2 ± 5.2 years. There was no significant difference between the two groups in terms of age (p = 0.12), gender (p = 0.32), and BMI (p = 0.067). In the AS group, ESR (p< 0.001), CRP (p < 0.001), uric acid (p<0.001) was significantly higher whereas direct Bb (P = 0.016) were significantly lower than controls. In correlation analysis, Bb parameters and disease activity parameters were negatively correlated with each other. When we divided the group according to ASDAS_CRP> 3.5, direct Bb (p = 0.020), total Bb (p = 0.029) and AST (p = 0.004) were significantly lower in high activity group (N = 25) and ESR (p = 0.000) was significantly higher. Conclusion: The direct Bb in patients with AS were found significantly low and negatively correlated with disease activity, this supports the role of oxidative stress in AS disease pathogenesis. Bb can be used as a biomarker in diagnosis and follow up in AS disease.